2019
DOI: 10.1152/ajpcell.00145.2019
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II deteriorates advanced atherosclerosis by promoting MerTK cleavage and impairing efferocytosis through the AT1R/ROS/p38 MAPK/ADAM17 pathway

Abstract: Vulnerable plaques in advanced atherosclerosis have defective efferocytosis. The role of ANG II in the progression of atherosclerosis is not fully understood. Herein, we investigated the effects and the underlying mechanisms of ANG II on macrophage efferocytosis in advanced atherosclerosis. ANG II decreased the surface expression of Mer tyrosine kinase (MerTK) in macrophages through a disintegrin and metalloproteinase17 (ADAM17)-mediated shedding of the soluble form of MerTK (sMer) in the medium, which led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…In addition, P38 was reported to be involved in the regulation of efferocytosis. Zhang et al found that angiotensin II damages efferocytosis in advanced atherosclerosis, which is involved in P38 pathway [62]. Recently, D Gilroy et al reported that inhibition of the elevated p38 MAPK could restore efferocytosis and enhance the inflammatory resolution in the elderly [63], indicating targeting P38 could be a potent strategy to modulate chronic inflammation via efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, P38 was reported to be involved in the regulation of efferocytosis. Zhang et al found that angiotensin II damages efferocytosis in advanced atherosclerosis, which is involved in P38 pathway [62]. Recently, D Gilroy et al reported that inhibition of the elevated p38 MAPK could restore efferocytosis and enhance the inflammatory resolution in the elderly [63], indicating targeting P38 could be a potent strategy to modulate chronic inflammation via efferocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Promotion of macrophage autophagy [38]; (b) Efficient efferocytosis of apoptotic bodies [36]. Cytotoxic CD8 + T lymphocyte (Tc) depletion [100] CD8α or CD8β targeted monoclonal antibody Regulatory T lymphocyte (Treg) promotion [101].…”
Section: Cell Survival Promotion Approachmentioning
confidence: 99%
“…For appropriate efferocytosis, a Mer Tyrosine Kinase (MerTK) expressed on the macrophage surface is required and pathways, which promote MerTK shedding from a membrane to the soluble form, impair this process. For instance, angiotensin II negatively affects efferocytosis through ADAM17 activation and subsequent MerTK shedding [ 38 ]. Apart from the aspects of cellular death, interventions preventing macrophage conversion into foam cells (such as inhibition of LOX-1, a receptor recognizing and internalizing oxLDL particles) as well as reverse cholesterol transport promotion in foam cells via LXRα receptor activation have been demonstrated to be atheroprotective in animal models [ 39 , 40 , 41 ].…”
Section: Approaches Directed At Specific Molecular Pathwaysmentioning
confidence: 99%
“…157 Ang II induces shedding of MerTK off the cell membrane through AT1R/ROS/p38MAPK/ADAM17 pathway. 158 Consequently, Ang II impairs switching M1 to M2. Continuation of pro-inflammatory status result in activation of MMPs and inducing of ECM remodeling processes.…”
Section: A New Insight To Pathophysiology Of Ards In Covid19mentioning
confidence: 99%